Pay as you go system versus Fully funded pension in Peru (2013)
The following paper analyses the sustainability of the Peruvian “Pay as You Go System” which is provided by the Government -- In Peru, the “Pay as you Go System” coexists with Private Pension Funds or “Fully Funded Pension” -- Sometimes both systems compete with each other with advantages and disadvantages between them -- We found that “Pay as You Go System” cannot be sustainable over a long period of time -- In addition, based on a comparative analysis of advantages and disadvantages, we propose some recommendations to make Private Pension Funds (Fully Funded Pension) the best alternative to Pay as You Go System